PENGARUH BAHAN ORGANIK TERHADAP KADAR AIR TANAH DAN PERTUMBUHAN TANAMAN JAGUNG DI LAHAN KERING - Eko Murniyanto (Universitas Tribhuwana Tunggadewi, 2007)
Abstract Effects of low quality organic matter application at rates of 5, 10, and 15 t/ha on soil water content and yield of maize have been studied on a dry land area of Wonogiri. The organic matters used for this study were Acasia auriculiformis, Gigantochloa apus and Sacharum officinarum litters. Results of the study showed that application of organic matter at all rates significantly increased water content and decreased C/N ratio of the soil, but did not affect water holding capacity of the soil. These changes have in turn significantly affected leaf area index, growth rate, number seed per pod, weight of 100 seeds and maize harvesting index